2020
DOI: 10.1021/acsanm.0c01879
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Texture and Composition on Graphene Growth by Chemical Vapor Deposition on Cu–Ni Alloys for Field Emission Application

Abstract: The present investigation is aimed to find a thread between various surface textures of polycrystalline Cu−Ni alloys, in cold-rolled and annealed conditions, and the nature of graphene, grown by the chemical vapor deposition (CVD) method, on these substrates. High-quality graphene grown on Cu−Ni alloys was transferred to various nanostructures, such as CuO nanorods and carbon nanotubes, for field emission application. In this work, , and 63Cu−37Ni) alloy buttons were prepared by arc melting, and texture in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…It is observed that overwhelming of the evolution of the C texture happens during annealing, if the sample contains a strong Bs component after deformation. 58 The effect of friction is credited for the development of a high fraction of Bs components and a low fraction of cube-oriented grains. A similar texture after annealing could be anticipated, only when the materials experience extended recovery or continuous recrystallization.…”
Section: Recrystallization Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that overwhelming of the evolution of the C texture happens during annealing, if the sample contains a strong Bs component after deformation. 58 The effect of friction is credited for the development of a high fraction of Bs components and a low fraction of cube-oriented grains. A similar texture after annealing could be anticipated, only when the materials experience extended recovery or continuous recrystallization.…”
Section: Recrystallization Mechanismmentioning
confidence: 99%
“…In these applications, the surface texture of the substrate was found to be a crucial factor for the growth of graphene. [1][2][3][4][5][6] The functional properties of graphene on the substrate depend on the uniformity and crystallinity of the graphene film, which can be achieved by the epitaxial growth of the film on the substrate. 7,8 Ni/Cu alloys have been widely used as substrates for second-generation HTS tapes, and a firm cube texture of the Ni/Cu alloy substrate is required for the epitaxial growth of HTS films.…”
Section: Introductionmentioning
confidence: 99%
“…The gas pressure regulation in a circulating CVD system can thus be utilized to overcome the self-limiting growth . Not only on conventional metal catalysts but, by controlling the process parameters, graphene growth on other catalysts such as copper/nickel alloys, , dielectric substrates, like SiO 2 /Si, , and sapphire can also be modulated.…”
Section: Introductionmentioning
confidence: 99%